Semiotic Analysis of the Meaning of Masculinity in the Lyrics of the song "Risalah Hati" DEWA 19 - Novianto, Riski (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2024)
Music is a medium for communication, music is also often used as a means to encourage sympathy about the reality that is happening. Because music is played from children to adults, from waking up to before going to bed. Thus, music can also be an inspiration for people who listen to it, because the music played encourages someone to act, behave, and can even change their lifestyle. The research method used is a qualitative research method with a qualitative descriptive approach. Meanwhile, the analysis technique used is Ferdinand de Saussure's semiotic analysis technique. Ferdinand de Saussure's semiotic theory focuses on signified and signified as well as syntagmatic and paradigmatic relationships. This research found that the meaning of masculinity in the lyrics of the song "Risalah Hati" by Dewa 19 illustrates that someone living in the world is always in pairs. A form of strength (power) from a man, an aura of courage, aggression, and emphasis on every action becomes something meaningful when a man is in love. Masculinity in the lyrics of the song "Risalah Hati" also teaches us how to be rational in loving ourselves and loving others. Keywords: Music, Semiotic, Dewa 19